Bodies of Work: Sexual Circulations in Philippine Cinema - Flores, Patrick D. (Humanities Diliman: A Philippine Journal of Humanities; Vol 1 No 1 (2000), 2007)
Excerpt The most recent skirmish between the MTRCB and certain sectors denouncing the slew of soft-pornographic films circulating during the second half of 1999 takes us to the heart of the problem of sex as a "regulatory ideal," a norm that renders material the limits and differences embedded within such contentious categories as morality, decency, customs, the "prestige" of the State, and, indeed, the commission of error in custom. This mode of enforcement reiterates itself over time and through bodies at work in the constitution of the politic underwriting the said categories. And because of such sufferance, sex can only serve as a means to generate power to produce the image and likeness of its naturalized condition as well as the strange articulations of repression. The ways in which in the most recent "word war" involving the Chief Censor and a moral crusader, who used to preside over the same office, would exchange heated words pertaining to the "homosexuality" of the latter and the "prostitution" of the former have, in fact, sexualized the debate, and so channeling all energies to the problematic of sexual regulation in society.